2023
DOI: 10.2144/fsoa-2023-0108
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Performance of Pretreatment Systemic Immune-Inflammation Index in Women with Epithelial Ovarian Cancer

Kehinde S Okunade,
Sarah O John-Olabode,
Adaiah P Soibi-Harry
et al.

Abstract: Purpose: This study investigated the prognostic performance of the systemic immune-inflammation index (SII) in patients with epithelial ovarian cancer (EOC) in Lagos, Nigeria. Methods: We performed a secondary analysis of the data of 91 women who had treatment for EOC between 2009 and 2018. The associations between pretreatment SII and survivals were tested. Results: Pretreatment SII more than 610.2 was a significant independent predictor of reduced progression-free survival (HR = 2.68; 95% CI, 1.17 to 6.09) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this respect, investigators worldwide came to demonstrate that a higher number of platelets associated with a higher number of circulating neutrophils and monocytes and a lower level of lymphocytes significantly influenced the long-term outcomes of ovarian cancer. Moreover, this correlation proved to be present even when studying the influence of certain ratios such as the platelet-to-lymphocyte ratio, lymphocyteto-monocyte ratio, neutrophil-to-lymphocyte ratio [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, investigators worldwide came to demonstrate that a higher number of platelets associated with a higher number of circulating neutrophils and monocytes and a lower level of lymphocytes significantly influenced the long-term outcomes of ovarian cancer. Moreover, this correlation proved to be present even when studying the influence of certain ratios such as the platelet-to-lymphocyte ratio, lymphocyteto-monocyte ratio, neutrophil-to-lymphocyte ratio [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wang et al underlined the fact that dynamic modifications of SII at six weeks postoperatively in patients with hepatocarcinoma had a predictive value in identifying cases with improved prognosis after resection [28]. Meanwhile, it seems that this parameter is useful for estimating the extent of the disease in peritoneal carcinomatosis from ovarian or colorectal origin [20][21][22][23][24][25] as well as the therapeutic response at chemotherapy alone or in association with monoclonal antibodies. Therefore, a recent study conducted on patients with peritoneal carcinomatosis from ovarian cancer demonstrated that patients presenting a pretreatment value of SII over 730 did not benefit after adjusting bevacizumab to standard chemotherapy alone while cases presenting a lower value of this parameter reported a significantly improved outcome after bevacizumab association [29].…”
Section: Discussionmentioning
confidence: 99%